2002
DOI: 10.1016/s0928-8244(02)00280-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of a 13.8-kDa bacteriolytic enzyme from house dust mite extracts: homology with prokaryotic proteins suggests that the enzyme could be bacterially derived

Abstract: Bacteriolytic activity was detected in extracts of whole mite and spent growth medium (SGM) from the clinically important Dermatophagoides pteronyssinus and Dermatophagoides farinae mites and was most abundant in whole mite extract. Gram-positive organisms Micrococcus lysodeikticus, Bacillus megaterium and Listeria monocytogenes were preferentially lysed and the lytic activity was enhanced by thiols, destroyed by mite proteases, inhibited by HgCl2 and high concentrations of NaCl but was resistant to heat and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 43 publications
1
20
3
Order By: Relevance
“…In house dust mites, Dermatophagoides pteronyssinus and D. farinae, lysozyme activity has been reported in both whole mite extracts (WME) and spent growth medium extracts (SGME), i.e., an extract of the medium after mite cultivation, containing faeces and debris of the rearing diet without mites (Childs and Bowman 1981;Mathaba et al 2002;Stewart et al 1998). It was suggested that group 2 mite allergens of D. pteronyssinus displayed lysozyme activity, but the Der p2 lacked lysozyme activity (Hakkaart et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In house dust mites, Dermatophagoides pteronyssinus and D. farinae, lysozyme activity has been reported in both whole mite extracts (WME) and spent growth medium extracts (SGME), i.e., an extract of the medium after mite cultivation, containing faeces and debris of the rearing diet without mites (Childs and Bowman 1981;Mathaba et al 2002;Stewart et al 1998). It was suggested that group 2 mite allergens of D. pteronyssinus displayed lysozyme activity, but the Der p2 lacked lysozyme activity (Hakkaart et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2. Alignment of a partial sequence of 14.5-kDa bacteriolytic enzyme in D. pteronyssinus (Mathaba et al 2002), with deduced amino-acid sequences of the gene fragment retrieved from D. farinae (this work), and corresponding parts of the closest homologs found in bacteria (Streptomyces sp., Mycobacterium sp., Gordonia effusa) and fungi (Aspergillus terreus, Metarhizium anisopliae, Beauveria bassiana, and Cordyceps militaris). Numbering according to the D. pteronyssinus protein.…”
Section: Resultsmentioning
confidence: 99%
“…Although the protein showed bacteriolytic activity and molecular mass similar to lysozymes, the sequence analysis indicated similarity to prokaryotic P60 proteins (Mathaba et al 2002). In the current study, we identiÞed a homologous protein in D. farinae.…”
mentioning
confidence: 98%
See 2 more Smart Citations